Positive electrode active material, positive electrode active material layer, all-solid-state lithium ion battery, method for manufacturing positive electrode active material, and method for manufacturing all-solid-state lithium ion battery
The use of Li x Ti 2x-1 Mn 2-3x O or Li x Nb x-0.5 Mn 1.5-2x O with an irregular rock salt structure addresses the deterioration issue in positive electrode materials, ensuring high capacity retention in all-solid-state lithium ion batteries by avoiding electrolyte-related degradation.
Patent Information
- Application Number
- JP2022129337
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-08-15
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2042-08-15
AI Technical Summary
Deterioration of positive electrode active materials in lithium ion secondary batteries due to repeated charging and discharging, particularly in liquid-based systems, is a significant issue.
Development of a positive electrode active material with a general formula Li x Ti 2x-1 Mn 2-3x O(0.500
The proposed active material effectively suppresses deterioration in all-solid-state lithium ion batteries, maintaining high capacity retention rates, unlike liquid-based systems, where deterioration is primarily due to electrolyte interactions.
Smart Images

Figure 0007619341000002 
Figure 0007619341000003 
Figure 0007619341000004
Abstract
Description
Technical Field
[0001] The present disclosure relates to a positive electrode active material, a positive electrode active material layer, an all-solid-state lithium-ion battery, a method for manufacturing a positive electrode active material, and a method for manufacturing an all-solid-state lithium-ion battery.
Background Art
[0002] Patent Document 1 discloses a positive electrode active material for a lithium-ion secondary battery having a rock salt-type structure represented by the general formula: Li x Ti 2x-1 Mn 2-3x O (0.50 < x < 0.67) and having an average particle size of 0.5 μm or less.
Prior Art Documents
Patent Documents
[0003]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0004] One of the causes of capacity degradation due to repeated charge and discharge of a lithium-ion secondary battery is deterioration of the positive electrode active material.
[0005] The main object of the present disclosure is to provide a positive electrode active material capable of suppressing deterioration of the positive electrode active material due to repeated charge and discharge of a lithium-ion secondary battery.
Means for Solving the Problems
[0006] The present inventors have found that the above problems can be achieved by the following means: 《Aspect 1》 General formula: Li x Ti 2x-1 Mn 2-3x O (0.500 < x < 0.650) or general formula: Li x Nb x-0.5 Mn1.5-2x A positive electrode active material for an all-solid-state lithium-ion secondary battery, represented by O(0.500 < x < 0.650) and having an irregular rock salt structure. <<Aspect 2>> The positive electrode active material according to Aspect 1, wherein at least a part of the surface is coated with a LiNbO3 film. <<Aspect 3>> A positive electrode active material layer containing the positive electrode active material according to Aspect 1 or 2. <<Aspect 4>> The positive electrode active material layer according to Aspect 3, further containing a sulfide solid electrolyte. <<Aspect 5>> An all-solid-state lithium-ion secondary battery having the positive electrode active material layer according to Aspect 3 or 4. <<Aspect 6>> It has a positive electrode current collector layer, the positive electrode active material layer, a solid electrolyte layer, a negative electrode active material layer, and a negative electrode current collector layer in this order. The all-solid-state lithium-ion secondary battery according to Aspect 5. <<Aspect 7>> Mixing Li2CO3, Mn2O3, and TiO2 or NbO2 by ball milling, firing to obtain a product, and Grinding the product by ball milling, A method for producing the positive electrode active material according to Aspect 1 or 2, comprising: <<Aspect 8>> A method for manufacturing an all-solid-state lithium-ion secondary battery, comprising laminating a positive electrode current collector layer, the positive electrode active material layer according to Aspect 3, a solid electrolyte layer, a negative electrode active material layer, and a negative electrode current collector layer in this order.
Advantages of the Invention
[0007] The present disclosure can mainly provide a positive electrode active material capable of suppressing deterioration of the positive electrode active material due to repeated charge and discharge of a lithium-ion secondary battery.
Brief Description of the Drawings
[0008] [Figure 1] It is a schematic diagram of an all-solid-state lithium-ion secondary battery 1 according to one embodiment of the present disclosure. [Diagram 2]1 is a graph showing X-ray diffraction patterns of the powder prepared in Example 1 before and after treatment with a dry ball mill. [Diagram 3] 1 is a graph showing charge / discharge curves of the all-solid-state lithium ion secondary battery of Example 1. [Figure 4] 2 is a graph showing charge / discharge curves of the liquid lithium ion secondary battery of Comparative Example 1. [Diagram 5] 1 is a graph showing cycle test results of the all-solid-state lithium ion secondary battery of Example 1. [Figure 6] 1 is a graph showing the results of a cycle test of the all-solid-state lithium ion secondary battery of Example 2. [Figure 7] 1 is a graph showing cycle test results of the all-solid-state lithium ion secondary battery of Example 3. [Figure 8] 1 is a graph showing the results of a cycle test of the all-solid-state lithium ion secondary battery of Example 4. [Figure 9] 1 is a graph showing cycle test results of the liquid lithium ion secondary battery of Comparative Example 1. [Figure 10] 13 is a graph showing the results of a cycle test of the liquid lithium ion secondary battery of Comparative Example 2. [Figure 11] 13 is a graph showing the results of a cycle test of the liquid lithium ion secondary battery of Comparative Example 3. [Figure 12] 13 is a graph showing the results of a cycle test of the liquid lithium ion secondary battery of Comparative Example 4. [Figure 13] 13 is a graph showing charge / discharge curves at the 10th and 20th cycles of the all-solid-state lithium ion secondary battery of Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, embodiments of the present disclosure will be described in detail. Note that the present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the present disclosure.
[0010] 1.Cathode active material The cathode active material of the present disclosure is a cathode active material for an all-solid-state lithium-ion secondary battery. The cathode active material of the present disclosure has the general formula: Li x Ti 2x-1 Mn 2-3x O (0.500 < x < 0.650) or the general formula: Li x Nb x-0.5 Mn 1.5-2x O (0.500 < x < 0.650), and has an irregular rock-salt structure.
[0011] Here, x may be greater than 0.500, 0.520 or more, 0.540 or more, 0.560 or more, or 0.580 or more, and may be less than 0.650, 0.630 or less, 0.610 or less, or 0.590 or less.
[0012] Specifically, x may be, for example, 0.535, 0.555, 0.570, or 0.585. Examples of compounds in which x has such values include, for example, Li 1.07 Ti 0.13 Mn 0.80 O2, Li 1.11 Ti 0.22 Mn 0.67 O2, Li 1.14 Ti 0.29 Mn 0.57 O2, and Li 1.17 Ti 0.33 Mn 0.50 O2.
[0013] Although not limited by theory, the principle by which the deterioration due to repeated charge and discharge of a lithium-ion secondary battery can be suppressed in the cathode active material of the present disclosure is considered as follows.
[0014] Some materials used as cathode active materials for liquid-based lithium-ion secondary batteries may deteriorate due to irreversible structural changes and mechanical degradation associated with the use of the battery. Therefore, even when such materials are used as cathode active materials for all-solid-state lithium-ion secondary batteries, they may deteriorate in the same manner as when used as cathode active materials for liquid-based lithium-ion secondary batteries.
[0015] General formula: Lix Ti 2x-1 Mn 2-3x O (0.500 < x < 0.650) or general formula: Li x Nb x-0.5 Mn 1.5-2x O (0.500 < x < 0.650), and when the cathode active material having an irregular rock salt structure is used as the cathode active material of a liquid-based lithium ion secondary battery, it may deteriorate with the use of the battery. However, the deterioration of these cathode active materials is not due to irreversible structural changes and mechanical degradation, but rather due to the presence of an electrolytic solution, such as the desorption of O and the elution of Mn into the electrolytic solution due to the reaction with the electrolytic solution. Therefore, when these cathode active materials are used as the cathode active material for an all-solid-state lithium ion secondary battery, which is a lithium ion secondary battery that does not use an electrolytic solution, the deterioration of the cathode active material due to repeated charge and discharge of the lithium ion secondary battery is suppressed.
[0016] In other words, the invention of the present disclosure is based on the finding that a compound represented by the general formula: Li x Ti 2x-1 Mn 2-3x O (0.500 < x < 0.650) or general formula: Li x Nb x-0.5 Mn 1.5-2x O (0.500 < x < 0.650) and having an irregular rock salt structure is suitable for use as a cathode active material for an all-solid-state lithium ion battery based on the above properties.
[0017] In the present disclosure, a liquid-based lithium ion secondary battery is a lithium ion secondary battery that uses an electrolytic solution as an electrolyte. On the other hand, in the present disclosure, an all-solid-state lithium ion secondary battery is a lithium ion secondary battery in which the electrolyte is a solid electrolyte.
[0018] The cathode active material of the present disclosure can be coated with a LiNbO3 film on at least a part of its surface.
[0019] The positive electrode active material of the present disclosure can be produced by a production method including, for example, mixing Li2CO3, Mn2O3, and TiO2 or NbO2 in a ball mill, calcining the mixture to obtain a product, and pulverizing the product in a ball mill.
[0020] More specifically, powders of Li2CO3, Mn2O3, and TiO2 or NbO2 may be mixed with an organic solvent, such as ethanol, in a wet ball mill. The wet ball mill may be performed, for example, at a rotation speed of 100 to 1000 rpm for 5 to 30 minutes, with a 1 to 5 minute interval between each cycle repeated 5 to 30 times. After the wet ball milling, cold isostatic pressing (CIP) may be performed before firing. The CIP may be performed at 100 to 500 MPa for 1 to 30 minutes.
[0021] The firing may be carried out in an air atmosphere at 600 to 1000° C. for 5 to 20 hours.
[0022] The ball mill for pulverizing the product may be a dry ball mill. The dry ball mill may perform 1 to 5 sets of 20 to 60 cycles of mixing at 400 to 1000 rpm for 5 to 30 minutes and leaving an interval of 1 to 5 minutes.
[0023] 2.Cathode active material layer The positive electrode active material layer of the present disclosure is a positive electrode active material layer for an all-solid-state lithium ion secondary battery. The positive electrode active material layer of the present disclosure contains the positive electrode active material of the present disclosure, and optionally a solid electrolyte, a conductive assistant, and a binder.
[0024] The positive electrode active material layer of the present disclosure can be formed, for example, by depositing a positive electrode mixture slurry, in which the positive electrode active material of the present disclosure, and an optional solid electrolyte, a conductive assistant, a binder, and the like are dispersed in a solvent, for example, an organic solvent, on a substrate and drying the slurry. The substrate may be, for example, a metal foil, and may also serve as a positive electrode current collector layer.
[0025] 2-1.Solid electrolyte The material of the solid electrolyte is not particularly limited, and any material that can be used as a solid electrolyte for use in a lithium ion secondary battery can be used. For example, the solid electrolyte may be, but is not limited to, a sulfide solid electrolyte, an oxide solid electrolyte, or a polymer electrolyte.
[0026] Examples of sulfide solid electrolytes include, but are not limited to, sulfide-based amorphous solid electrolytes, sulfide-based crystalline solid electrolytes, and argyrodite-type solid electrolytes. Specific examples of sulfide solid electrolytes include Li2S-P2S5-based (Li7P3S 11 , Li3PS4, Li8P2S9, etc.), Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-P2S5-GeS2(Li 13 GeP3S 16 , Li 10 GeP2S 12 ), LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li 7-x P.S. 6-x Cl x etc.; or combinations thereof, but are not limited to these.
[0027] An example of an oxide solid electrolyte is Li7La3Zr2O 12、 Li 7-x La3Zr 1-x Nb x O 12、 Li 7-3x La3Zr2Al x O 12 , Li 3x La 2 / 3-x TiO3, Li 1+x Al x Ti 2-x (PO4)3, Li 1+x Al x Ge 2-x (PO4)3, Li3PO4, or Li 3+x PO 4-x N x (LiPON), but is not limited to these.
[0028] The sulfide solid electrolyte and the oxide solid electrolyte may be glass or crystallized glass (glass ceramic).
[0029] Examples of the polymer electrolyte include, but are not limited to, polyethylene oxide (PEO), polypropylene oxide (PPO), and copolymers thereof.
[0030] 2-2.Conductive assistant The conductive assistant is not particularly limited. For example, the conductive assistant may be, but is not limited to, a carbon material such as Ketjen Black (KB), vapor grown carbon fiber (VGCF), acetylene black (AB), carbon nanotube (CNT), carbon nanofiber (CNF), carbon black, coke, graphite, and carbon nanofiber, and a metal material.
[0031] 2-3. Binder The binder is not particularly limited. For example, the binder may be, but is not limited to, a material such as polyvinylidene fluoride (PVdF), butadiene rubber (BR), polytetrafluoroethylene (PTFE), or styrene butadiene rubber (SBR), or a combination thereof.
[0032] 3. All-solid-state lithium-ion secondary battery The all-solid-state lithium ion secondary battery of the present disclosure has the positive electrode active material layer of the present disclosure. The all-solid-state lithium ion secondary battery of the present disclosure can have a positive electrode current collector layer, a positive electrode active material layer of the present disclosure, a solid electrolyte layer, a negative electrode active material layer, and a negative electrode current collector layer, in this order.
[0033] FIG. 1 is a schematic diagram of an all-solid-state lithium-ion secondary battery 1 according to one embodiment of the present disclosure.
[0034] As shown in FIG. 1, an all-solid-state lithium-ion secondary battery 1 according to one embodiment of the present disclosure includes, in this order, a positive electrode current collector layer 10, a positive electrode active material layer 20 of the present disclosure, a solid electrolyte layer 30, a negative electrode active material layer 40, and a negative electrode current collector layer 50.
[0035] The all-solid-state lithium ion secondary battery of the present disclosure can be produced, for example, by a production method including laminating a positive electrode current collector layer, a positive electrode active material layer of the present disclosure, a solid electrolyte layer, a negative electrode active material layer, and a negative electrode current collector layer in this order.
[0036] The method for stacking the layers is not particularly limited. For example, after each layer is formed individually, the layers may be stacked on top of each other in this order: a positive electrode collector layer, a positive electrode active material layer of the present disclosure, a solid electrolyte layer, a negative electrode active material layer, and a negative electrode collector layer.
[0037] 3-1. Positive electrode current collector layer The material used for the positive electrode current collector layer is not particularly limited, and any material that can be used as a current collector for a battery can be appropriately used.
[0038] For example, the material used for the positive electrode current collector layer may be, but is not limited to, stainless steel (SUS), aluminum, copper, nickel, iron, titanium, carbon, etc. Among these, the material for the positive electrode current collector layer is preferably aluminum.
[0039] The shape of the positive electrode current collector layer is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred.
[0040] 3-2.Solid electrolyte layer The solid electrolyte layer contains a solid electrolyte and, optionally, a binder, etc. For the solid electrolyte and the binder, the above descriptions regarding "2-1. Solid electrolyte" and "2-3. Binder" can be referred to, respectively.
[0041] 3-3.Negative electrode active material layer The negative electrode active material layer contains a negative electrode active material, and optionally a solid electrolyte, a conductive additive, and a binder.
[0042] The material of the negative electrode active material is not particularly limited, and may be metallic lithium, or may be a material capable of absorbing and releasing metal ions such as lithium ions. Examples of the material capable of absorbing and releasing metal ions such as lithium ions include, but are not limited to, alloy-based negative electrode active materials and carbon materials.
[0043] The alloy-based negative electrode active material is not particularly limited, and examples thereof include Si alloy-based negative electrode active materials and Sn alloy-based negative electrode active materials. The Si alloy-based negative electrode active material includes silicon, silicon oxide, silicon carbide, silicon nitride, and solid solutions thereof. The Si alloy-based negative electrode active material can include elements other than silicon, such as Fe, Co, Sb, Bi, Pb, Ni, Cu, Zn, Ge, In, Sn, Ti, and the like. The Sn alloy-based negative electrode active material can include tin, tin oxide, tin nitride, and solid solutions thereof. The Sn alloy-based negative electrode active material can include elements other than tin, such as Fe, Co, Sb, Bi, Pb, Ni, Cu, Zn, Ge, In, Ti, Si, and the like. Among these, the Si alloy-based negative electrode active material is preferred.
[0044] The carbon material is not particularly limited, and examples thereof include hard carbon, soft carbon, graphite, etc. For the solid electrolyte, the conductive additive, and the binder, the descriptions in "2-1. Solid electrolyte", "2-2. Conductive additive", and "2-3. Binder" above can be referred to, respectively.
[0045] 3-4. Negative electrode current collector layer The material and shape of the negative electrode current collector layer are not particularly limited, and the materials and shapes described in "3-1. Positive electrode current collector layer" above may be used. In particular, the material of the negative electrode current collector layer is preferably copper. The shape is preferably a foil. EXAMPLES
[0046] Examples 1 to 5 and Comparative Examples 1 to 4 Example 1 (Synthesis of positive electrode active material) MnCO3 powder was calcined in air at 700℃ for 12 hours to obtain Mn2O3 powder.
[0047] Next, Mn2O3 powder, TiO2 powder, Li2CO3 powder, and ethanol were placed in a pot (45 mL) in a specified mass ratio and mixed in a wet ball mill that performed 17 cycles of 15 minutes at 300 rpm and 3 minutes of rest time. The ZrO2 balls used in the wet ball mill were 5 pieces of 10 mm, 10 pieces of 5 mm, and 4 g of 1 mm.
[0048] The resulting mixture was subjected to cold isostatic pressing (CIP) at 250 MPa for 5 min.
[0049] Next, the boat-shaped aluminum boat containing the mixture was wrapped in Cu foil and sintered by heating at 900°C for 12 hours in an argon atmosphere to obtain a powder.
[0050] The obtained powder was placed in a pot (45 mL) and mixed by performing three sets of dry ball milling at 600 rpm for 15 minutes and 3 minutes of rest time, 40 times. Note that the powder on the wall of the pot was scraped off after each set. The number / amount of ZrO2 balls used in the dry ball mill was the same as that of the wet ball mill described above.
[0051] The obtained powder was Li 1.14 Ti 0.29 Mn 0.57 It was O2 powder.
[0052] (LiNbO3 coating) The obtained powder and an aqueous LiNbO3 solution were weighed, mixed in a mortar and dried to obtain a LiNbO3-coated positive electrode active material of Example 1. The amount of LiNbO3 coating relative to the mass of the positive electrode active material including the LiNbO3 coating was 10 mass%.
[0053] (Production of all-solid-state lithium-ion secondary batteries) The positive electrode active material of Example 1, the sulfide-based solid electrolyte, polyvinylidene fluoride (PVDF) as a binder, and vapor-grown carbon fiber (VGCF) were weighed in a mass ratio of 62.5:30.8:0.5:6.2, and dispersed and mixed in butyl butyrate to form a slurry. The slurry was dried at 165°C to prepare a positive electrode composite.
[0054] Li4Ti5O as a negative electrode active material 12 The sulfide-based solid electrolyte, PVDF, and VGCF were weighed in a weight ratio of 72.1:22.7:3.5:1.7, and dispersed and mixed in butyl butyrate to form a slurry. The slurry was dried at 165°C to prepare a negative electrode composite material.
[0055] A sulfide-based solid electrolyte was used as the separator layer, and the positive electrode mixture and the negative electrode mixture were pressed together to produce an all-solid-state battery.
[0056] Examples 2 to 4 The same procedure as in Example 1 was repeated except that the mass ratios of the Mn2O3 powder, TiO2 powder, and Li2CO3 powder used were changed. 1.17 Ti 0.33 Mn 0.50 O2, Li 1.11 Ti 0.22 Mn 0.67 O2 and Li 1.07 Ti 0.13 Mn 0.80 O2 powder was obtained.
[0057] Next, in the same manner as in Example 1, a LiNbO3 coating was formed to obtain the positive electrode active material of each example.
[0058] Moreover, in the same manner as in Example 1, an all-solid-state lithium ion secondary battery was produced.
[0059] Example 5 A positive electrode active material and an all-solid-state lithium ion secondary battery of Example 5 were produced in the same manner as in Example 1, except that the LiNbO3 coating was not formed.
[0060] Comparative Example 1 A liquid lithium ion secondary battery of Comparative Example 1 was produced using the positive electrode active material produced in Example 1. Specifically, the positive electrode active material produced in Example 1, PVDF, and acetylene black (AB) were weighed in a weight ratio of 76.5:10.0:13.5, and dispersed and mixed in N-methyl-2-pyrrolidone to form a slurry. The slurry was applied onto an Al current collector foil and vacuum dried overnight at 120°C to produce a positive electrode. A coin cell (CR2032) was produced using TDDK-217 (Daikin) as the electrolyte and metal Li foil as the negative electrode, and the liquid lithium ion secondary battery of Comparative Example 1 was produced.
[0061] Comparative Examples 2 to 4 Liquid lithium ion secondary batteries of Comparative Examples 2 to 4 were fabricated in the same manner as in Comparative Example 1, except that the positive electrode active materials fabricated in Examples 2 to 4, respectively, were used.
[0062] <X-ray crystal diffraction test> In Example 1, the powder before the dry ball mill and the powder after the dry ball mill were measured for diffraction patterns at 2θ=0 to 120° by X-ray diffraction pattern using CuKα.
[0063] The powder before the dry ball milling has the diffraction pattern shown in the upper part of Figure 2, which indicates high crystallinity of Li 1.14 Ti 0.29 Mn 0.57 Indicates that it is O2.
[0064] On the other hand, the powder after the dry ball milling had the diffraction pattern shown in the lower part of Figure 2, and a broad peak was observed, which is attributed to the irregular rock salt structure. This indicates that the powder after the dry ball milling contains low-crystalline Li 1.14 Ti 0.29 Mn 0.57 Indicates that it is O2.
[0065] <Charge / Discharge Test> The lithium ion batteries of each example were placed in a thermostatic chamber maintained at 60° C., and were subjected to 20 cycles of charge and discharge in the voltage range of 1.5-4.8 V and at a 0.1 C rate (1 C = 285 mAg-1).
[0066] The capacity retention rate of each example was calculated, where the capacity retention rate was the ratio of the discharge capacity after 20 cycles to the discharge capacity after 10 cycles.
[0067] The results of the charge / discharge tests of the lithium ion secondary batteries of Examples 1 to 4 and Comparative Examples 1 to 4 are shown in FIGS.
[0068] 3 and 4 are graphs showing charge / discharge curves at the time of initial charge / discharge of the lithium ion batteries of Example 1 and Comparative Example 1, respectively. As shown in Figs. 3 and 4, the all-solid-state lithium ion secondary battery of Example 1 had an initial charge / discharge capacity of 247 mAh / g. On the other hand, the liquid lithium ion secondary battery of Comparative Example 1 had an initial charge / discharge capacity of 263 mAh / g. The difference in charge / discharge voltage between Example 1 and Comparative Example 1 is due to the difference in the negative electrode.
[0069] In addition, as shown in Figs. x Ti 2x-1 Mn 2-3x All of the all-solid-state lithium-ion secondary batteries using O as the positive electrode active material had a high capacity retention rate of 99% or more. x Ti 2x-1 Mn 2-3x A liquid lithium-ion secondary battery that uses O as the positive electrode active material has a low capacity retention rate of about 60%.
[0070] Next, the relationship between the configurations of the lithium ion secondary batteries of Example 1, Example 5, and Comparative Example 1 and the charge / discharge retention ratio is shown in Table 1 below.
[0071] [Table 1]
[0072] As shown in Table 1, Examples 1 and 5 had a higher capacity retention rate than Comparative Example 1. Also, in Example 5, although the charge-discharge capacity during initial charge-discharge was lower than that in Example 1, it had a high charge-discharge capacity of 250 mAh / g and 257 mAh / g at the 10th cycle and 20th cycle, respectively. Also, a high capacity retention rate was obtained in Example 5 as well.
[0073] Note that, as shown in Fig. 13, in Example 5 where no LiNbO3 coating was formed, no significant difference was observed in the charge-discharge curves even at the 10th cycle and 20th cycle of charge-discharge.
[0074] Note that Nb, like Ti, does not have valence electrons and is known to have an effect of stabilizing lattice oxygen oxidized in the same manner as Ti. Therefore, for Li x Nb x-0.5 Mn 1.5-2x O(0.50 < x < 0.65), it is considered to exhibit the same behavior as Li x Ti 2x-1 Mn 2-3x O(0.50 < x < 0.65), and as shown in the above examples, it is considered that a high capacity retention rate can be obtained by using it as a positive electrode active material of an all-solid-state lithium-ion secondary battery.
Description of Reference Numerals
[0075] 1 All-solid-state lithium-ion secondary battery 10 Positive electrode current collector layer 20 Positive electrode active material layer 30 Solid electrolyte layer 40 Negative electrode active material layer 50 Negative electrode current collector layer
Claims
1. An all-solid-state lithium ion secondary battery having a positive electrode current collector layer, a positive electrode active material layer, a solid electrolyte layer, a negative electrode active material layer, and a negative electrode current collector layer in this order, the positive electrode active material layer contains a positive electrode active material and a sulfide solid electrolyte, The positive electrode active material is represented by the general formula: Li x Ti 2x-1 Mn 2-3x O (0.50<x<0.65) or general formula: Li x Nb x-0.5 Mn 1.5-2x O (0.50<x<0.65), has a disordered rock salt structure, and is represented by LiNbO 3 At least a portion of the surface is covered with the coating. All-solid-state lithium-ion secondary battery.
2. The positive electrode active material is represented by the general formula: Li x Ti 2x-1 Mn 2-3x 2. The all-solid-state lithium ion secondary battery according to claim 1, wherein x is represented by the formula: O (0.50<x<0.65).
3. The positive electrode active material is represented by the general formula: Li x Nb x-0.5 Mn 1.5-2x 2. The all-solid-state lithium ion secondary battery according to claim 1, wherein x is represented by the formula: O (0.50<x<0.65).
4. The all-solid-state lithium ion secondary battery according to any one of claims 1 to 3, wherein the positive electrode active material does not contain an ion species selected from a phosphate ion, a sulfate ion, a borate ion, a silicate ion, an aluminate ion, a germanate ion, a nitrate ion, a carbonate ion, and a halide ion.
Citation Information
Patent Citations
Negative electrode for sulfide all-solid battery and sulfide all-solid battery
JP2020030919A
Positive electrode active material for lithium ion secondary battery, positive electrode for lithium ion secondary battery, lithium ion secondary battery, electronic device, and vehicle
WO2017122663A1
Amorphous oxide-based positive electrode active material, method for producing same and use of same
WO2017169599A1